2005
DOI: 10.1109/tasc.2005.849678
|View full text |Cite
|
Sign up to set email alerts
|

Inductor design for cryogenic power electronics

Abstract: The core losses of a number of ferrite compositions as well as several metallic ferromagnetic materials have been measured at 78 K. From these measurements we can estimate the power dissipation of a conventional inductor (copper windings, magnetic core) at low temperature. It is found that the magnetic losses generally increase on cooling; this counteracts the reduction in copper losses, and the dissipation would not be much different than its room temperature value. If superconducting windings are substituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…The measurements have shown that the loss of a cold core at 77 K is increased by more than a factor of 10 compared to the loss at room temperature. Our magnetic loss measurements agree quantitatively with the results published in [31]. Finally, we determine the quality-factor (Q-factor) of the coils, which is defined as…”
Section: Ac Loss Measurementssupporting
confidence: 85%
“…The measurements have shown that the loss of a cold core at 77 K is increased by more than a factor of 10 compared to the loss at room temperature. Our magnetic loss measurements agree quantitatively with the results published in [31]. Finally, we determine the quality-factor (Q-factor) of the coils, which is defined as…”
Section: Ac Loss Measurementssupporting
confidence: 85%
“…Conventional inductors experience an increase in magnetic losses and a reduction in copper losses when operated at cryogenic temperatures, resulting in no overall benefit or disadvantage over their room temperature performance [21].…”
Section: Capacitors and Inductors 1) Operation And Performancementioning
confidence: 99%
“…[1] Its excellent soft magnetic properties have been attributed to the very fine microstructure that results in nearly zero effective magnetocrystalline anisotropy [2,3] and very small magnetostriction. [4] Due to its successful room temperature performance, a recent study by Claassen [5] investigated Finemet for use in cryogenic environments to support superconducting motor and cryogenic power converter technologies. The study revealed that the core losses of Finemet increase by nearly 300 pct compared to its room temperature value.…”
Section: Introductionmentioning
confidence: 99%
“…Other materials designed for room temperature use have also been investigated for cryogenic applications, exhibiting varying degrees of degraded performance. [5][6][7][8][9] With all of the materials investigated showing some performance degradation due to the cryogenic environment, it is clear that there is room for new alloys specifically designed for cryogenic temperatures if ferromagnetic materials are going to be considered for use within the cryostat.…”
Section: Introductionmentioning
confidence: 99%